Digital public administration and e-government in developing nations : policy and practice - Halpin, Edward F., (IGI Global, 2013)
"In recent years, it has become apparent that there are very distinct gaps between developed and developing regions in the world, especially in regards to e-government systems, infrastructures, and processes. This book examines e-government from the perspective of developing nations and addresses issues and concerns of developing systems and processes"--Provided by publisher.